Conformation and structural compaction of scleroglucan biopolymers as witnessed by FRET spectroscopy - Virgili Alemán, Inés María (2011)
Scleroglucans from Sclerotium rolsfii ATCC 201126 produced at fermenter scale and ethanol recovered at different times (EPS I: 48 h and EPS II: 72 h) did not exhibit significant variations in MW, degree of polymerization or branching, and adopted a triple helical semirigid structure in aqueous neutral solution. However, they showed certain differences in rheological behaviour, anti-syneresis, emulsifier and suspending properties, hydrogel microstructure and their ability to activate LAL and Glucatell coagulation tests. That may be related to different conformational features such as the triplex expansion degree, which tried to be assessed by fluorescence resonance energy transfer (FRET) spectroscopy. Alkali denaturation of EPSs and subsequent renaturation events over time were evaluated by FRET. EPSs double-labelled with a donor/acceptor fluorophores pair (AP/FITC) were treated with increasing NaOH concentrations (0.015-1.00 M) and a gradual partial opening of the triple-helix rather than a complete strands separation was observed. An isopropanol-processed scleroglucan, EPSi (recovered at 72 h), and a commercial scleroglucan LSCL, also exhibited a similar behaviour. FRET results suggested a decreasing triplex compaction degree as follows: LSCL > EPS I > EPS II > EPSi. Renaturalization showed that even without neutralization the triple-helix conformation could be restored after 96 h.